2020
DOI: 10.1128/jvi.00336-20
|View full text |Cite
|
Sign up to set email alerts
|

A Virion-Based Assay for Glycoprotein Thermostability Reveals Key Determinants of Filovirus Entry and Its Inhibition

Abstract: Ebola virus (EBOV) entry into cells is mediated by its spike glycoprotein (GP). Following attachment and internalization, virions traffic to late endosomes where GP is cleaved by host cysteine proteases. Cleaved GP then binds its cellular receptor, Niemann-Pick C1. In response to an unknown cellular trigger, GP undergoes conformational rearrangements that drive fusion of viral and endosomal membranes. The temperature-dependent stability (thermostability) of the pre-fusion conformers of ‘Class I' viral … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…A previous report implicated the reduced stability of the A82V mutant as the basis for its increased infectivity in vitro and in vivo ( 10 ). Likewise, proteolysis has a destabilizing effect on GP that is thought to promote fusion activation ( 24 26 ). Accordingly, we set out to investigate the stability of GP mutants in both uncleaved and precleaved states using an ELISA that measures the thermostability of an epitope spanning GP1 and GP2 ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous report implicated the reduced stability of the A82V mutant as the basis for its increased infectivity in vitro and in vivo ( 10 ). Likewise, proteolysis has a destabilizing effect on GP that is thought to promote fusion activation ( 24 26 ). Accordingly, we set out to investigate the stability of GP mutants in both uncleaved and precleaved states using an ELISA that measures the thermostability of an epitope spanning GP1 and GP2 ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…All FDA-approved drugs tested, amiodarone, bepridil, clomifene, sertraline, and toremifene, significantly hampered GP CL -NPC1 interaction measured by in situ PLA. Previous reports focused on bepridil, sertraline, and toremifene, which were proposed to destabilize GP’s prefusion conformation by binding into a cavity at the GP 1 -GP 2 interface in silico and in vitro ( 35 , 38 , 39 ). Our data also indicated changes in the intracellular distribution and morphology of NPC1 + LE/LY, as well as NPC1’s cholesterol transporter function following drug incubations.…”
Section: Discussionmentioning
confidence: 99%
“…The unprecedented EBOV outbreak in West Africa from 2013 to 2016 uncovered a pressing need for anti-EBOV therapeutics; since then, numerous studies screened for and characterized FDA-approved drugs with anti-filoviral activity. The most promising drug candidates, amiodarone, bepridil, clomifene, sertraline, and toremifene, were reported to block one or several steps during EBOV entry (15,(33)(34)(35)(36)(37)(38)(39). As their precise mechanisms of anti-EBOV activity still remain elusive, we examined the capacity of these inhibitors to alter intracellular GP CL -NPC1 interaction in the PLA.…”
Section: Figmentioning
confidence: 99%
“…A previous report implicated the reduced stability of the A82V mutant as the basis for its increased infectivity in vitro and in vivo (10) . Likewise, proteolysis has a destabilizing effect on GP that is thought to promote fusion activation (23)(24)(25) .…”
Section: The Gp Destabilizing Effect Of the A82v Mutation Is Unmaskedmentioning
confidence: 99%
“…Accordingly, we set out to investigate the stability of GP mutants in both uncleaved and pre-cleaved states, using an ELISA that measures the thermostability of an epitope spanning GP1 and GP2 (25) . By measuring the half-maximal melting temperature (T m ) of GPs, we found that uncleaved GPs bearing 544I were significantly less stable than their 544T counterparts ( Figure 4A and 4C ).…”
Section: The Gp Destabilizing Effect Of the A82v Mutation Is Unmaskedmentioning
confidence: 99%